Eosinophil Purification from Peripheral Blood of Rhesus Monkeys - Legrand, Fanny (Methods in molecular biology (Clifton, N.J.), 2021)
Eosinophils are granulocytes involved mainly in allergic inflammation and parasitic responses and constitute 1-5% of the circulating leukocytes in human healthy subjects. New immunotherapies targeting eosinophils have been developed and evaluated recently, and the availability of animal models that could mimic human eosinophil responses is important to consider. Differences in eosinophil biology and pathogenesis between humans and murine models have limited their utility in some settings. Isolation of viable eosinophils from rhesus macaque blood suitable for ex vivo and in vitro experimentation could provide a valuable tool for the study of eosinophil-targeted therapies and for the exploration of eosinophilic associated responses. Here, a new technique for the isolation of human eosinophils from rhesus macaque blood by negative selection from whole blood is described.